Preparation method of novel stimulation-responsive foam
By using common commercial surfactants and the same charge nanoparticles as composite foaming agents and using the triggering mechanism of anion and cation pairs, a simple and easy-to-operate stimulus-responsive foam preparation is achieved, and complex synthesis in the prior art is solved and the problem of poor stability significantly improves the stability and circulation performance of the foam.
Patent Information
- Application Number
- CN202411235904.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-02-18
AI Technical Summary
The existing preparation methods for stimulus-responsive foams are complex, requiring high concentrations of switching surfactants, and the foam stability is poor, making it difficult to achieve repeated cycle foaming and defoaming processes.
Using ordinary commercial surfactants and the same charge nanoparticles as composite foaming agents, the foam disappears through the triggering mechanism of the anion and cationic pairs, and the foam is regenerated by adding cationic surfactants to achieve repeated cycle foaming- Defoaming process.
It realizes simple and easy-to-operate stimulus-responsive foam preparation, avoids the synthesis of complex functional materials, significantly improves the stability and circulation performance of the foam, and has higher practical value.
Smart Images

Figure CN119455710A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a method for preparing a novel stimulus-responsive foam, belonging to the field of colloid and interface chemistry. Background Art
[0002] Foam is a gas / liquid dispersion system, that is, the gas is dispersed in the liquid in the form of small bubbles, in which the gas is the dispersed phase and the liquid is the continuous phase. The size of the bubbles is visible to the naked eye and belongs to a coarse dispersion system. Experience shows that pure liquids generally cannot foam. In order to obtain stable foam, the liquid used must include more than two components, that is, in addition to the liquid itself, it must contain a foaming agent. Surfactants are typical foaming agents, so aqueous solutions of surfactants are easy to produce foam. Surfactants are adsorbed at the gas / liquid interface and belong to dynamic equilibrium. Under certain conditions, they can be rapidly adsorbed and desorbed, so the dispersed system formed is a metastable or thermodynamically unstable system. At the same time, solid particles with surface activity can also stabilize foams. They are adsorbed at the gas / liquid interface to form a thermodynamically stable system, which is called Pickering foam. In previous studies, it was found that ordinary inorganic nanoparticles can be hydrophobized in situ and turned into surfactant particles through electrostatic interaction with ionic surfactants with opposite charges, thereby stabilizing Pickering foams.
[0003] Foam is widely used in industrial technology fields such as foam separation, foam flotation, foam fire extinguishing, and foam oil recovery. It is also closely related to our daily life and has important applications in foam baths, shaving creams, toothpaste, washing and decontamination, and preparation of foaming foods.
[0004] In practical applications, foams are often required to remain temporarily stable and to defoam quickly after use. This has given rise to a new type of foam: switchable or stimulus-responsive foams. To some extent, they belong to intelligent systems and are responsive, so they are currently receiving more and more attention. Since the stability of foams mainly depends on the foaming agent, switchable foams can be prepared by corresponding switchable foaming agents. To date, people have obtained switchable surfactants with various triggering mechanisms, such as redox, pH, light, temperature, CO2 / N2, etc. However, the switchable foams prepared with switchable surfactants are thermodynamically unstable systems and require higher concentrations (>cmc). In addition, some switchable or stimulus-responsive surfactant particles with pH response, temperature response, light response, pH-temperature response, magnetic field strength-temperature response, and pH-ionic strength response have also been reported, which can stabilize the corresponding switchable or stimulus-responsive Pickering foams. However, they are almost all functional polymers or inorganic / organic hybrids, and their synthesis process is relatively complicated and difficult.
[0005] The present invention attempts to provide a method for preparing a novel stimuli-responsive foam. A novel structure is obtained by using a common commercial surfactant and nanoparticles of the same charge as a composite foaming agent. The trigger mechanism of anion-cation pairs is then used to make the foam disappear. This foaming-defoaming-refoaming cycle can be repeated to obtain a stimuli-responsive foam. The method is simple and easy to operate, avoids the synthesis of complex functional materials, provides a new idea for the preparation of stimuli-responsive foams, and makes the relevant technology more practical. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a novel stimulus-responsive foam. The foam is stabilized by an ionic surfactant and nanoparticles with the same charge. The composite foaming agent is composed of unmodified nano aluminum oxide particles and a cationic surfactant, wherein the primary particle size of the particles is 10-200nm, the concentration used is 0.3% to 2.0% by mass (based on the aqueous phase), the carbon chain length of the cationic surfactant is 12-18, including quaternary ammonium salts, pyridinium ammonium salts, and imidazoline ammonium salts, and the concentration used is 0.05 to 10 times its critical micelle concentration (based on the aqueous phase). The nanoparticles are dispersed in an aqueous solution of the cationic surfactant, and by means of the synergistic effect between the inorganic nanoparticles and the ionic surfactant with the same charge, a stable water-based foam is obtained by hand shaking. Through the trigger mechanism of anion-cation pairs, an anionic surfactant anion (the carbon chain length of the anionic surfactant is 12-18, and the hydrophilic group is sulfate, carboxylate, or sulfonate) is added to the stable foam, and the foam disappears after shaking. When the cationic surfactant with the same concentration as the initial concentration is added, the foam is regenerated after shaking, and the foam volume is similar to the foam volume obtained by the first foaming. This defoaming-refoaming cycle can be repeated to form a stimulus-responsive foam.
[0007] Another object of the present invention is to provide a dispersion system. It contains the composite foaming agent of the present invention. The water phase contains inorganic nanoparticles, and the interface between the water phase and the air phase is adsorbed with an ionic surfactant; and the inorganic nanoparticles and the ionic surfactant carry the same charge in the water phase. The microstructure of the thus-stabilized foam is different from that of ordinary foam and Pickering foam, wherein a low concentration of surfactant is adsorbed on the water / air interface, giving the bubble surface charge, and the nanoparticles are distributed in the water phase to form a thicker water film, which increases the distance between the bubbles and greatly reduces the van der Waals attraction between the bubbles. The bubbles are prevented from agglomerating through the repulsive action of the double electric layer between particles, bubbles, and bubbles, thereby forming a stable foam.
[0008] Another object of the present invention is to provide a stimulus-responsive trigger mechanism. This trigger mechanism is an ion pair formed by anionic and cationic surfactants. The cationic surfactants in the aqueous phase interact with the nanoparticles of the same charge to form stable foam. Once an equimolar amount of anionic surfactants is added to the system, the latter tends to form ion pairs with the cationic surfactants, causing them to be unable to stabilize the foam, thereby causing the foam to disappear. When the cationic surfactants are added to the system at the same initial concentration, they can interact with the nanoparticles of the same charge again, and the foam is regenerated. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 This is a scanning electron microscope image of the nano-aluminum oxide particles (DK-Al2O3-30) of the present invention;
[0010] Figure 2 (A) is the effect of Al2O3 particles in water dispersion, taken immediately after shaking, with mass fractions of 0.3%, 0.5%, 1%, and 2% (relative to the water phase); (B) is the effect of CTA aqueous solution, taken immediately after shaking; (C) is the effect of 0.5% Al2O3 particles and different concentrations of CTAB co-stabilized foam, taken immediately after shaking; CTAB ((B) and (C), from left to right): 1x10 -5 , 3x10 -5 , 6x10 -5 , 1x10 -4 , 3x10 -4 , 6x10 -4 , 1x10 -3 , 3x10 -3 , 6x10 -3 , 1x10 -2 mol / L;
[0011] Figure 3 The curves of the foam volume at different time intervals when CTAB is used alone to stabilize the foam and when 0.5% nano-Al2O3 particles / CTAB (different concentrations) are used together to stabilize the foam as a function of CTAB concentration; the foam volume was taken immediately after shaking (V0), and after 30 minutes (V 0.5 ), 24h later (V 24 );
[0012] Figure 4 (A) is a foam effect image stabilized by CTA alone, taken 24 hours after shaking; (B) is a foam effect image stabilized by 0.5% Al2O3 particles and different concentrations of CTAB, taken 48 hours after shaking; (C) is a foam effect image stabilized by 0.5% Al2O3 particles and different concentrations of SDS, taken 48 hours after shaking; CTAB / SDS concentration ((AC), from left to right): 1x10-5 , 3x10 -5 , 6x10 -5 , 1x10 -4 , 3x10 -4 , 6x10 -4 , 1x10 -3 , 3x10 -3 , 6x10 -3 , 1x10 -2 mol / L;
[0013] Figure 5 (A) is 0.5% Al2O3+3x10 -4 mol / L CTAB; (B) is 3x10 -4 mol / L CTAB; (C) 0.5% Al2O3+3x10 -4 mol / L SDS-stabilized foam micrograph, taken immediately after shaking;
[0014] Figure 6 The foam effect diagram of 0.5% Al2O3 particles and different concentrations of polyoxyethylene (6) dodecanol ether was taken immediately after shaking; polyoxyethylene (6) dodecanol ether concentration (from left to right): 1x10 -5 , 3x10 -5 , 6x10 -5 , 1x10 -4 , 3x10 -4 , 6x10 -4 , 1x10 -3 , 3x10 -3 , 6x10 -3 , 1x10 -2 mol / L;
[0015] Figure 7 Containing 0.5% nano-Al2O3 particles and 3×10 -4 mol / L CTAB aqueous dispersion was prepared by sequentially adding equimolar amounts of SDS and 3×10 -4 The effect of defoaming-foaming cycle with mol / L free CTAB was taken 10 minutes after shaking;
[0016] Figure 8 Micrographs of the original foam (a) and restabilized foam (c), (e), (g), (i). DETAILED DESCRIPTION
[0017] In order to facilitate a further understanding of the present invention, the following embodiments are provided to illustrate it in more detail. These embodiments are only for narration and are not intended to limit the scope or implementation principle of the present invention.
[0018] Embodiment 1:
[0019] Surface activity test of nano-aluminum oxide particles. Weigh 0.03, 0.05, 0.1 and 0.2 g of commercial nano-aluminum oxide particles (DK-Al2O3-30, primary particle size about 30 nm (see Figure 1 ), produced by Beijing Dekedaojin Technology Co., Ltd.), put it into a 25mL cylindrical bottle (6.5cm high, 2.5cm in diameter), add 10mL of pure water, and use an ultrasonic disperser (JYD-650, Shanghai) to disperse the particles in water (50W, 1min). The concentrations of the particles are 0.3%, 0.5%, 1% and 2% by mass (relative to the water phase). Transfer the dispersion to a 50mL stoppered measuring cylinder, cover the stopper, and oscillate up and down 20 times. No foam can be formed. Figure 2 (A) shows that the commercial nano-aluminum oxide particles used have no surface activity.
[0020] Embodiment 2:
[0021] Preparation of the novel foam. A series of aqueous solutions of different concentrations were prepared with octadecyltrimethylammonium bromide (CTAB, a product of Singma). 10 mL of each solution was placed in a 50 mL stoppered measuring cylinder and shaken up and down 20 times. Figure 2 As shown in (B), when the concentration of CTAB is less than 1x10 -4 mol / L, the single CTAB system cannot produce foam at all after oscillation. -4 mol / L, foam gradually began to form, but the foam was not stable enough and almost disappeared after 24 hours. If 0.05g Al2O3 (mass fraction 0.5%) particles were dispersed in the above CTAB aqueous solution, after shaking, when the CTAB concentration was greater than 3×10 -5 mol / L, stable foam can be formed, and as the CTAB concentration increases, the foam volume also increases ( Figure 2 (C)). Within the same surfactant concentration range, the dispersion containing particles produces much more foam than the single surfactant solution, and a certain amount of foam volume is still present after 24 h.
[0022] Figure 3 The variation of foam volume with surfactant concentration at different time intervals after foaming is given. The number after V in the legend represents the time after foaming in hours, where 0 means that foaming has just been completed.
[0023] Embodiment 3:
[0024] The formation mechanism of the new foam was verified. After a period of time, the foam wall in the single CTAB system and the foam wall in the Al2O3-CTAB mixed system became significantly thinner, and no nano-aluminum oxide was visible on the foam film. Figure 4 As shown in (A) and (B), it shows that the nano-aluminum oxide particles do not exist on the bubble surface.
[0025] 0.05 g Al2O3 (mass fraction 0.5%) particles were dispersed in 10 mL of aqueous solution of sodium dodecyl sulfate (SDS, Singma) of different concentrations, and the mixture was shaken up and down 20 times to produce foam. Figure 4 (B) and (C) show that, unlike the Al2O3-CTAB system, the water phase of the Al2O3-SDS system is mostly clear, while the water phase of the Al2O3-CTAB system is more turbid. After the foam disappears, some white particles can be seen attached to the wall of the stoppered measuring cylinder of the Al2O3-SDS system, while the wall of the Al2O3-CTAB system is very clean with no particles attached. Observation under a microscope ( Figure 5 ), it can also be found that in the Al2O3-SDS mixed system, the surface of the bubble is very rough. This is because the positively charged particles and the anionic surfactant interact through electrostatic interaction, and the particles are adsorbed on the gas / liquid interface after being hydrophobized in situ, thereby stabilizing the foam. This foam stabilized by particles is called Pickering foam. In the microphotographs of the foam formed by the Al2O3-SDS mixed system and the foam formed by the single CTAB, the surface of the bubble is very smooth. It can be seen that in the Al2O3-CTAB composite foaming agent, the aluminum oxide particles are not adsorbed on the gas / liquid interface, and the cationic CTAB is adsorbed on the water / air interface, giving the bubble surface charge, while the positively charged aluminum oxide particles are distributed in the water phase to form a thicker water film, which increases the distance between bubbles and greatly reduces the van der Waals attraction between bubbles. The bubbles are prevented from agglomerating through the repulsive action of the double electric layer between particles-particles, bubbles-bubbles, and particles-bubbles, thereby forming a stable foam. Since the microstructure of this foam is different from that of ordinary foam and Pickering foam, we call it a new type of foam. For this new type of foam, both the nanoparticles and the surfactant must be charged. If the cationic surfactant is replaced with a nonionic surfactant (polyoxyethylene (6) dodecanol ether), the nano-Al2O3 particles cannot produce a double-layer repulsion with the uncharged polyoxyethylene (6) dodecanol ether, so a stable foam cannot be obtained. Figure 6 shown.
[0026] Embodiment 4:
[0027] Stimulus-responsiveness verification of the new foam. A foaming system was selected, 0.5% nano-Al2O3 particles were dispersed in 3×10 -4 mol / L CTAB aqueous solution, take 10cm 3 Dispersion was placed in 50cm 3 The foam was shaken up and down 20 times to obtain rich foam with a volume of about 18cm 3 ,like Figure 7 (A) is shown. Subsequently, 0.1 g (cm 3 ) concentration is 3×10 -2 mol / L SDS aqueous solution (the molar number of SDS added is equal to that of CTAB in the system), after sufficient shaking, the foam almost completely disappears, such as Figure 7 (B) As shown. Then add 0.1g (cm 3 ) concentration is 3×10 -2 mol / L CTAB aqueous solution, foam is generated again after shaking, and the foam volume is almost the same as the foam volume obtained by the first foaming. Figure 7 (C). Repeat this process ( Figure 7 (DJ)) for five cycles.
[0028] Figure 8 Figure 2 is a micrograph of the original foam and a series of re-stabilized foams. As can be seen from the figure, the bubble size of the stable foam obtained in each cycle is basically the same, that is, the bubble size is reversible in the cycle, indicating that the stability of the bubble depends only on the concentration of free CTAB in the aqueous solution. This shows that we have obtained a new type of stimuli-responsive foam using the ion pair trigger mechanism.
[0029] Experimental data show that a new type of foam structure can be obtained by using common commercial surfactants and nanoparticles of the same charge. Then, using anion-cation pairs as a trigger mechanism to make the foam disappear, this foaming-defoaming-refoaming cycle can be repeated, thus obtaining a new type of stimuli-responsive foam.
[0030] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above examples. The above examples and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a novel stimuli-responsive foam, wherein the foam is stabilized by an ionic surfactant and nanoparticles with the same charge. The stimuli-responsiveness of the foam is triggered by an anion-cation pair.
2. The foaming agent for stable foam according to claim 1, which is composed of unmodified nano aluminum oxide particles and cationic surfactants, wherein the primary particle size of the particles is 10-200nm, the use concentration is 0.3% to 2.0% by mass fraction (based on the aqueous phase), the carbon chain length of the cationic surfactant is 12-18, including quaternary ammonium salts, pyridinium ammonium salts, and imidazoline ammonium salts, and the use concentration is 0.05 to 10 times its critical micelle concentration (based on the aqueous phase).
3. The novel foam described in claim 1 has a microstructure different from that of ordinary foam and Pickering foam, wherein a low concentration of surfactant is adsorbed on the water / air interface, giving the bubble surface charge and determining the size of the bubble, while the nanoparticles are distributed in the water phase to form a thicker water film, which increases the distance between the bubbles and greatly reduces the van der Waals attraction between the bubbles. The repulsive effect of the double electrical layer between particles, bubbles, and bubbles, prevents the bubbles from agglomerating, thereby forming a stable foam.
4. A method for preparing a novel stimulus-responsive foam according to claim 1, when an anionic surfactant anion (the carbon chain length of the anionic surfactant is 12-18, and the hydrophilic group is sulfate, carboxylate, or sulfonate) is added to the stable foam, the foam disappears after shaking, and when the cationic surfactant with the same concentration as the initial concentration is added, the foam is regenerated after shaking, and the foam volume is similar to the foam volume obtained by the first foaming. This defoaming-refoaming cycle can be repeated.
Citation Information
Cited By
Gold enhanced flotation method based on electrochemical bubble interface electronic state regulation and control
CN122057634A